A study on the purification of diatomite in hydrochloric acid - Goren, R; Baykara, T; Marsoglu, M (WILEY, 2002)
This paper describes the purification of diatomaceous earth mined in the Ankara region of Turkey. The diatomaceous earth was found to be essentially amorphous, but a small amount of crystalline illite, K0.7Al2(Si,Al)(4)O-10(OH)(2), was present in it. The complete chemical composition of the material was 74.4% SiO2, 14.55% Al2O3, 3.62% Fe2O3, 1.55% CaO, 1.37% MgO, 2.44% K2O and 0.72%Na2O. In connection with the purification of the diatomite, two different processing routes were planned: (1) leaching of the diatomaceous earth directly in cold acidic solutions of HCl; (ii) leaching of the diatomaceous earth directly by using hot 1 and 2N HCl. It was found that all of the undesirable elements in the composition of the diatomaceous earth were dissolved when treated at about 100degreesC with acidic solutions prepared using 1 and 2N HCl for various leaching times. Under several cold acid concentrations, varying from 1N to 5N HCl, however, only a small amount of silica is dissolved, while significantly reducing the contribution of undesirable aluminium, calcium, magnesium, iron and alkaline elements.
Keywords: diatomite; purification; leaching; Metallurgy & Metallurgical Engineering